Gelling agent for aqueous liquids

By wrapping powder or granular water-absorbing resin in water permeable and water-soluble polymer films, and undergoing silicic acid treatment and silicone-ica surface treatment, the problem of slow gel speed and easy breakage in water in the prior art is solved, and faster gel effect and higher strength are achieved.

JP7671457B2Active Publication Date: 2025-05-02KYOTO CHEM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020110204
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-26
Publication Date
2025-05-02
Estimated Expiration
2040-06-26

AI Technical Summary

Technical Problem

In the prior art, the improved gel material is slower in water-immersion and is prone to breaking during transportation and processing.

Method used

The water-absorbent resin is encased in a film with water permeability and water-soluble polymer sealing, and the water-absorbent resin is treated with silicic acid and is surface treated with a combination of hydrogen philic and hydrogen phobic silicon.

Benefits of technology

The gel speed of the hydrogel material is significantly improved, making it gel faster in water, while enhancing the strength of the material and avoiding breakage during transportation and processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671457000001
    Figure 0007671457000001
Patent Text Reader

Abstract

To provide a gelation material for an aqueous liquid material which more quickly converts an aqueous liquid material into gel than a conventional gelation material.SOLUTION: A gelation material for an aqueous liquid material is obtained by wrapping a powdery and / or granular water-absorbing resin by a sheet, and sealing the resin, in which at least a part of the sheet is water permeable, at least a part of the sealed part is sealed by a water-soluble polymer having a weight average molecular weight of 1,000-1,000,000, a water absorption magnification of the water-absorbing resin for pure water is 80-1,000 times, a content of a water-soluble component is 5 wt.% or less, and the water-absorbing resin is treated with silica.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gelling material for aqueous liquids, and more particularly to a gelling material for aqueous liquids that contains a specific water-absorbing resin. [Background technology]

[0002] Conventionally, as a bag-shaped gelling material that can be put into an aqueous liquid to gel (solidify), a material in which a water-absorbent resin is wrapped in a laminated sheet made by bonding a water-disintegrating paper and a water-soluble film is known (for example, Patent Document 1). However, the strength of the laminated sheet is insufficient, and there is a problem that it weakens especially when dry and the bag breaks during transportation or handling. To improve this, a gelling material for aqueous liquids (Patent Document 2) has been proposed and used, which is a gelling material in which a powdery and / or granular water-absorbent resin is wrapped and sealed in a sheet, at least a part of the sheet is water-permeable, and at least a part of the sealed part is sealed with a water-soluble polymer having a weight-average molecular weight of 1,000 to 1,000,000. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 4-239087 [Patent Document 2] Patent No. 4123404 Summary of the Invention [Problem to be solved by the invention]

[0004] However, when the above-mentioned improved gelling material is immersed in an aqueous liquid, it takes a long time for the gelling material to break down and gel the aqueous liquid, which can lead to problems during the process. Therefore, a gelling material that can gel more quickly has been desired.

[0005] An object of the present invention is to provide a gelling material for aqueous liquids that can gel an aqueous liquid more quickly than conventional gelling materials. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention provides a gelling material comprising a powdery and / or granular water-absorbent resin wrapped and sealed in a sheet, At least a part of the sheet is water permeable, and at least a part of the sealed portion is sealed with a water-soluble polymer having a weight average molecular weight of 1,000 to 1,000,000; The water absorbent resin has a water absorption capacity of 80 to 1000 times for pure water, and a water-soluble component content of 1% by weight or less; The water-absorbent resin is treated with silica, The water-absorbing resin Hydrophilic silica and hydrophobic silica are used in combination. Treated with silica There are The gelling material for aqueous liquids is characterized in that

[0008] The present invention is further characterized in that the water-soluble polymer is polyvinyl alcohol. Effect of the Invention

[0010] The gelling material of the present invention can provide a gelling material for aqueous liquids that can gel an aqueous liquid more quickly than conventional gelling materials. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1(a) is a perspective view showing the structure of an absorbent sandbag in accordance with the present invention, and FIG. 1(b) is a perspective view showing the absorbent sandbag of FIG. 1(a) in a swollen state after being immersed in water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the following embodiments. Various modifications can be made to the following embodiments within the same and equivalent scope of the present invention.

[0013] In the present invention, the powdered or granular water-absorbent resin is not particularly limited and may be either natural or synthetic, but it is preferable that the resin is inexpensive, has excellent water-absorption properties such as safety, durability, water absorption capacity and water retention, and is free from risk of spoilage. Examples of such water-absorbing resins include synthetic water-absorbing resins, and are not particularly limited as long as they absorb and retain water, but include, for example, partially neutralized polyacrylic acid crosslinked products, neutralized starch-acrylic acid graft polymers, hydrolyzates of starch-acrylonitrile graft polymers, saponified vinyl acetate-acrylic acid ester copolymers, crosslinked isobutylene-maleic anhydride copolymers, hydrolyzates of acrylonitrile copolymers or acrylamide copolymers or crosslinked products thereof, crosslinked acrylate-acrylamide copolymers, crosslinked polyvinyl alcohol, crosslinked modified polyethylene oxide, crosslinked acrylamide-2-methylpropanesulfonate copolymers, crosslinked (meth)acryloylalkanesulfonate copolymers, crosslinked carboxymethylcellulose salts, crosslinked polymers of cationic monomers, etc. Among these, partially neutralized polyacrylic acid crosslinked products and neutralized starch-acrylic acid graft polymers are preferred because of their particularly good water-absorbing properties, safety, and economical properties.

[0014] The above water-absorbing resins may be used alone or in a suitable mixture of two or more kinds. The water-absorbing resin is preferably in a particulate form, and may be in any shape, such as irregularly crushed, spherical, scaly, fibrous, rod-like, lump, or powder form, but is more preferably in a powder form from the viewpoint of water absorption speed.

[0015] The average particle size of the particles is not particularly limited, but is preferably 30 to 850 μm, and more preferably 60 to 500 μm. The water absorption ratio is 80 to 1000 times, and more preferably 100 to 800 times. If the water absorption ratio is less than 80 times, the degree of swelling after absorbing water is insufficient. If it exceeds 1000 times, the water absorption rate decreases because the water is absorbed during storage. The gel strength of the water-absorbent resin is 10,000 to 50,000 dynes / cm 2 is preferable, and more preferably 20,000 to 50,000 dynes / cm 2 The gel strength is 10,000 dynes / cm 2 If the strength is more than this, the force that pushes open the sealed portion of the bag after swelling is strong. The water absorbency and gel strength were measured by the following method.

[0016] [Method for measuring water absorption capacity] 0.2 g of water-absorbent resin adjusted to a particle size of 30 to 100 mesh (150 to 500 μm) was placed in a tea bag (20 cm long, 10 cm wide) made of 250 mesh nylon netting, and the bag was immersed in 500 ml of pure water for 1 hour to absorb water. The bag was then hung for 15 minutes to drain, after which the increase in mass was measured to determine the water absorption ratio relative to pure water.

[0017] [Method for measuring gel strength] The amount of absorbed saline solution (Mg / g) of the absorbent resin was measured in advance by the same tea bag method (based on JIS K7223-1996) as that used for the above absorption capacity measurement. (M×0.75) g of saline solution was placed in a 100 cc beaker, and 1 g of absorbent resin (150-250 microns) was added while stirring at 600 rps to absorb the solution uniformly, producing a smooth-surfaced absorbent gel. This absorbent gel was kept at 25°C, and the gel strength was measured using a neo-card meter (Iio Electric Co., Ltd., M302 type) under the following conditions. Load: 200g Pressure-sensitive shaft diameter: 3mm Pressure axis drop speed: 0.36cm / sec

[0018] The water-soluble component content is usually 5% by weight or less, and preferably 1% by weight or less. The smaller the content, the better. If the water-soluble component content exceeds 5% by weight, the aqueous liquid cannot be gelled as quickly as before. The water-soluble component content can be controlled by the polymerization conditions. As a method for decreasing the water-soluble component content in the water-absorbent resin, for example, a method for increasing the molecular weight of the water-absorbent resin is preferable, and this can be achieved by adopting a method for decreasing the polymerization concentration, a method for increasing the crosslinking density, etc. In addition, since the water-soluble component has a small molecular weight and contains carboxylic acid, it is also possible to make it water-insoluble by crosslinking it by post-crosslinking. The water-soluble components can be measured by the gravimetric method or the galvanic drop method described in JP-A-2005-445 etc. The galvanic drop method is a method that uses a calibration curve.

[0019] In addition, the water-absorbing resin is a crosslinked polymer of a water-soluble monomer, and the amount of the remaining water-soluble monomer (e.g., acrylic acid) in the water-absorbing resin is preferably 100 ppm or less, more preferably 50 ppm or less. If it is 100 ppm or less, skin disorders such as itching of the skin in contact with the water-absorbing resin are unlikely to occur. As a method for lowering the amount of the remaining water-soluble monomer (e.g., acrylic acid), a method of adding a reducing substance after polymerization is highly effective, but it can also be achieved by increasing the polymerization conditions, for example, the molecular weight of the water-absorbing resin. Examples of the reducing substance include sodium sulfite, ascorbic acid, and amines (ammonia, monoethanolamine, etc.). The amount used is preferably 0.001 to 5% by weight relative to the water-absorbing resin.

[0020] In the present invention, the powdery and / or granular water absorbent resin is treated with silica. By treating with silica, the water absorption rate of the powdery and / or granular water absorbent resin is improved, and the gelation rate of the aqueous liquid can be improved.

[0021] As the hydrophilic silica, a wide variety of known hydrophilic silicas can be used, and among them, fumed silica having silanol groups (Si-OH groups) on the surface is preferred.

[0022] Examples of hydrophobic silica include finely powdered silica that is modified by covalently bonding alkyl groups or the like to silanol groups on the surface of finely powdered hydrophilic silica, and finely powdered silica that is modified by covalently bonding methyl groups is preferred because it has an appropriate degree of hydrophobicity. Examples of surface treatment agents that covalently bond alkyl groups or the like to silanol groups include one or more selected from the group consisting of dimethyldichlorosilane, hexamethyldisilazane, (meth)acrylsilane, octylsilane (e.g., trimethoxyoctylsilane, etc.), and aminosilane.

[0023] An example of a method for covalently bonding methyl groups to silanol groups on the surface is to react the silanol groups with dimethyldichlorosilane or the like. The number of methyl groups covering the surface of the silica can be controlled by the amount of dimethyldichlorosilane or the like to be reacted. The number is not particularly limited, but from the viewpoint of adjusting the hydrophobicity of the silica and from the viewpoint of making the gelation speed faster than conventional when the gelling agent is added to an aqueous liquid, it is preferable to have 1.0 to 4.0 methyl groups / nm2 based on the surface area of ​​the silica. 2 is preferable, and more preferably, 1.5 to 3.8 particles / nm 2 , particularly preferably 2.0 to 3.5 particles / nm 2 It is. The number of methyl groups can be measured from the relative ratio of the peak intensities of silanol groups and methyl groups on the silica surface by infrared spectroscopy, and the surface area can be determined by the BET method.

[0024] As the silica, hydrophilic silica is preferred. More preferably, hydrophilic silica and hydrophobic silica are used in combination. Treatment with hydrophilic silica further improves the water absorption rate of the water absorbent resin, and further improves the gelation rate. Use in combination further improves the water absorption rate of the water absorbent resin, and further improves the gelation rate.

[0025] As a method for treating a powdered and / or granular water absorbent resin with silica, the mixture is easily obtained by blending silica with a powdered and / or granular water absorbent resin and mixing them at preferably 0 to 50° C., more preferably 10 to 30° C. Preferably, 1 to 20 parts by weight, more preferably 2 to 7 parts by weight of silica are blended and mixed with respect to 100 parts by weight of the water absorbent resin. The mixing method is obtained by putting both of them in a container and stirring or shaking them.

[0026] The sheet for wrapping the powdered and / or granular water-absorbent resin used in the present invention is at least partially water-permeable. Such a sheet may be flexible, but the form and material are not particularly limited as long as the sheet has a wet strength sufficient to not immediately break due to the swelling force of the water-absorbent resin when the water-absorbent resin is wrapped and sealed in the sheet and immersed in an aqueous liquid. In addition, the sheet must have a normal strength of a certain level or more sufficient to not break during transportation or other operations.

[0027] Here, the permeability is 100 cm 2 The time (seconds) required for the paper to pass through the area is 30 seconds or less, preferably 15 seconds or less, and particularly preferably 5 seconds or less. The normal strength must be 2 kg / cm or more, preferably 3 kg / cm or more, in both the vertical and horizontal directions, and the wet strength (tensile strength after immersion in ion-exchanged water at 25°C for 1 minute) must be 0.05 kg / cm or more, preferably 0.1 kg / cm or more. Conventional water-disintegrating paper, etc., is not necessarily preferred because its wet strength is too low.

[0028] In the present invention, the method of imparting water permeability to a sheet includes forming through holes in the sheet to allow water to pass through, and also covering the part where the through holes are formed with a water-soluble polymer by laminating it with a water-soluble sheet, so that the water-soluble resin dissolves in water and the holes become permeable immediately, thereby expressing water permeability. The size of the through holes is not particularly limited as long as water can pass through them, but is preferably 0.1 to 1 mm, particularly preferably 0.1 to 0.5 mm, and may be any size that does not allow the water-absorbent resin powder and / or particles to leak easily. Examples of the sheet having such through holes include fabrics such as knitted fabrics, woven fabrics, and nonwoven fabrics; mesh films such as polyethylene and polypropylene sheets with many fine holes formed therein, and the like. The thickness of the sheet is preferably 0.1 to 5 mm.

[0029] As the material for forming the sheet, for example, synthetic resins or fibers such as polyester, nylon, acrylic, polyethylene, polypropylene, polystyrene, etc. and their modified products, semi-synthetic fibers such as rayon and acetate, natural fibers such as cotton, wool, silk, pulp fibers, etc., and their blends and woven products can be applied to all fiber materials. Among these, sheets made of hydrophilic fibers such as cotton, hemp, pulp fibers, and nylon are preferred, and sheets made of cotton and / or pulp are more preferred. This is because water easily enters the through holes due to the hydrophilicity of the material forming the sheet. Sheets made of non-hydrophilic materials are preferably used after being hydrophilized with a surfactant or the like. Here, the index of hydrophilicity is that a material such as fiber is cut into a size of 1.5 cm x 1.5 cm, floated on ion-exchanged water at 25°C, and completely wetted or sunk within 10 minutes, and non-hydrophilic materials do not get wet with water even after 10 minutes.

[0030] The water-soluble polymer that covers the portion where the through holes are formed can be the same as the water-soluble polymer described below. The sheet used in the present invention is partially or entirely composed of such a sheet. Two or more of such sheets may be used in combination.

[0031] In the present invention, in order to encapsulate the powdery and / or granular water-absorbent resin, at least a part of the sealed portion is sealed with a water-soluble polymer, that is, the water-soluble polymer is present between the sheets of the sealed portion and then sealed. The water-soluble polymer used for sealing is water-soluble after the sheets are bonded by the seal and must have a weight-average molecular weight of 1000 to 1 million. Preferably, the weight-average molecular weight is 2000 to 500,000, and particularly preferably 5000 to 200,000. If the weight-average molecular weight is less than 1000, the adhesive strength is weak and the gelling material may peel off during transportation or operation. If the weight-average molecular weight exceeds 1 million, it dissolves slowly in water and the time required for gelling of the aqueous liquid is delayed. Specific examples of such water-soluble polymers include the following (1) to (3).

[0032] (1) Synthetic polymer Polyvinyl alcohol (POVAL; the degree of saponification is not limited as long as it is soluble in water, but is preferably 70 to 98 mol %, and particularly preferably 75 to 95 mol %), polyacrylamide, water-soluble acrylic resins (homo- or copolymers of water-soluble monomers such as sodium acrylate and hydroxyethyl acrylate), water-soluble polyurethane resins (reaction products of polyisocyanates such as isophorone diisocyanate and hexamethylene diisocyanate with polyols such as polyethylene oxide having a molecular weight of 400 to 4000, etc.), water-soluble epoxy resins (reaction products of polyols such as polyethylene oxide having a molecular weight of 400 to 4000 with polyepoxides such as ethylene glycol diglycidyl ether, etc.), polyethyleneimine, polyethylene oxide, polyvinylpyrrolidone, etc.;

[0033] (2) Semi-synthetic polymer Cellulose-based materials such as carboxymethyl cellulose, methyl cellulose, and hydroxyethyl cellulose; starch-based materials such as oxidized starch and modified starch;

[0034] (3) Natural polymer Starches such as corn starch, wheat starch, tapioca starch, potato starch, etc.; sugars such as konjac mannan and pectin; seaweeds such as funori, agar, and sodium alginate; vegetable mucilages such as gum arabic, guar gum, locust bean gum, carrageenan, abelmoschus aureus, and tragacanth gum; microbial mucilages such as dextran and pullulan; proteins such as glue, gelatin, and casein; Two or more of these may be used in combination. Of these, synthetic polymers are preferred, and polyvinyl alcohol is particularly preferred.

[0035] The form of the water-soluble polymer before sealing, that is, the form in which it is present between the sheets, may be, for example, one selected from a water-soluble film, a water-soluble coating agent, and a glue. The water-soluble film is preferably a water-soluble thermoplastic film. The weight-average molecular weight of the water-soluble polymer is preferably 5,000 to 1,000,000, and particularly preferably 10,000 to 500,000. The thickness of the film is not particularly limited, but is preferably 10μ to 4 mm, and particularly preferably 50μ to 2 mm. As the water-soluble coating agent, a water-soluble polymer having a weight-average molecular weight of preferably 1,000 to 500,000, and particularly preferably 5,000 to 200,000 can be used. Water-soluble adhesives are also included here.

[0036] The concentration of the coating agent is not limited as long as it can be applied with a brush, roller, etc., but is preferably 10 to 100% by mass. A solvent or water that is usually used to dilute the coating agent can be used. The powder may be applied and then thermally melted to adhere. The amount of coating agent applied is preferably 0.1 to 50 g / m2 in terms of the mass of solid content. 2 , and particularly preferably 0.2 to 20 g / m 2 The paste is preferably a water-soluble polymer having a weight-average molecular weight of 1,000 to 300,000, and particularly preferably 3,000 to 150,000. The concentration and application amount of the paste may be the same as those of the coating agent. Of these forms, the water-soluble film and the water-soluble coating agent are preferred, and the water-soluble film is particularly preferred.

[0037] The gelling material of the present invention is formed by wrapping and sealing a powdered and / or granular water-absorbent resin in a sheet. The form of encapsulation is not particularly limited, and an example of such a method is a method of forming a sheet into a bag shape. The method of manufacturing the gelling material is not particularly limited. When forming a sheet into a bag shape, the bag may be formed by stacking two sheets and sealing them, or by stacking three or more sheets. A bag may be formed by putting a water-absorbent resin into a partially open bag shape from the beginning and then sealing the open part. Examples of methods for forming a bag include a method of sealing a sheet except for a part, putting a water-absorbent resin in it, and then sealing the remaining part, and a method of placing a water-absorbent resin on a sheet and sealing its periphery.

[0038] The sealing method is not particularly limited as long as the sealed portion is sealed to such an extent that it will not peel off during transportation or handling of the gelling material, but is usually performed by heat sealing (thermal fusion), pressure bonding, etc. For the temperature for heat fusion, pressure bonding pressure, etc., conditions usually used can be used. The adhesive strength of the sheet is preferably 0.1 kgf / 25 mm or more, and more preferably 0.2 kgf / 25 mm or more. The sheet may be adhered to such an extent that the sealed portion does not peel off during transportation or handling of the gelling agent. The adhesive strength can be measured by the following method.

[0039] [Adhesive strength] The peel strength (180° peel strength, pulling speed 100 mm / min, unit: kgf / 25 mm) is measured using an adhesive strength measuring device.

[0040] When a water-soluble film or coating is used as a sealing material, a water-soluble film may be pasted or coated on one side of a sheet, and then the water-soluble film or water-soluble coating side of the sheet may be placed on the inside of the sealing portion and sealed, or the water-soluble film or coating side of one sheet may be placed on the inside and sealed with another sheet. A water-soluble film may be inserted between the sheets and sealed, or in the case of a coating, the sealing may be performed before the coating side dries. When a paste is used, the same procedure as for coating is followed, but it is particularly preferable to apply the paste only to the sealing portion. The paste may be inserted between the sheets, or the paste may be applied to one or both sheets, and then the paste-applied surfaces of the sheets are placed together and sealed. It is also possible to combine these methods. Of these, the method of sealing sheets with a water-soluble film pasted together or sheets coated with a coating agent is preferable. These methods are also efficient in terms of workability.

[0041] Of the total area of ​​the sheet used to encapsulate the powdered and / or granular water-absorbent resin, the area occupied by the water-permeable portion is preferably 25% or more, more preferably 50% or more, and particularly preferably 75% or more. It is most preferably 100%. If it is 25% or more, the amount of water that the water-absorbent resin can quickly absorb is supplied sufficiently quickly. The portion other than the water-permeable portion means that it does not have water permeability as described here, and refers to a portion that does not have through holes through which water can pass, or a portion that has through holes and is breathable but does not allow water to pass through. The material may be the same as that of the water-permeable portion.

[0042] The sheet is sealed after the powdered and / or granular water-absorbent resin is put in, and when the sheet is made into a bag, the ratio of the part sealed with the water-soluble polymer to the total periphery length of the sealed bag is preferably 25% or more, more preferably 50% or more, and particularly preferably 75% or more. Most preferably 100%. If it is 25% or more, the time for the water-absorbent resin to come out after the seal part is opened is short. It is preferable to seal the entire periphery of the bag with the water-soluble polymer. The remaining part not sealed with the water-soluble polymer may be sealed with a sealing material that is not a water-soluble polymer (such as a normal polyethylene sheet or polypropylene sheet) or sewn, but there is no particular limitation. The width of the seal is not particularly limited as long as the water-absorbent resin does not leak from the bag during handling, but is preferably 1 to 30 mm, and particularly preferably 5 to 15 mm.

[0043] The shape of the gelling material may be set according to the application, and when it is bag-shaped, it may be any shape such as a circle, a rectangle (rectangle, square, diamond, trapezoid, etc.), a triangle, etc., and is not particularly limited, but is preferably a rectangle. The size is also not particularly limited, but preferably one side of the rectangle (particularly a rectangle, etc.) is 5 to 30 cm, and particularly preferably 7 to 20 cm. If one side is 5 cm or more, the efficiency in producing the gelling agent is good, and if it is 30 cm or less, it is not too large and difficult to handle.

[0044] The amount of water-absorbent resin enclosed in one gelling material is preferably 0.01 to 0.6 g / cm 2 and more preferably 0.05 to 0.5 g / cm 2 and particularly preferably 0.1 to 0.4 g / cm 2 It is.

[0045] In addition to the water-absorbent resin, the gelling material of the present invention may contain, if necessary, known deodorants, fragrances, bactericides, fungicides, preservatives, antifoaming agents, foaming agents, antiblocking agents, surfactants, oxygen scavengers, bulking agents (CMC, etc.), etc. The amount of addition is not particularly limited as long as it is within a range that does not hinder the water-absorbent resin from absorbing water and swelling, but is preferably 50 parts by mass or less, more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin.

[0046] The gelling material of the present invention provides a gelling material for aqueous liquids that gels aqueous liquids more quickly than conventional gelling materials. The reason for this is believed to be as follows. When the gelling material of the present invention is immersed in an aqueous liquid, the water-soluble polymer acting as an adhesive on the surface of the sheet begins to dissolve in water, and at the same time, the powdered and / or granular water-absorbent resin absorbs the water that has entered the bag through the water-permeable parts of the sheet and swells, resulting in the swelling pressure pushing the adhesive surface of the sheet apart and making it easy to open the sealed part made of the water-soluble polymer. When the sealed part is opened, the water-absorbent resin comes out of the bag and absorbs water all at once, swelling and gelling the aqueous liquid.

[0047] The powdered and / or granular water absorbent resin is an aggregate of water absorbent resin. When water penetrates from the water permeable portion of the sheet and swells the powdered and / or granular water absorbent resin, if there is silica on the surface of the water absorbent resin, it penetrates quickly between the water absorbent resin in the powder and / or granules, and if the water soluble component of the water absorbent resin is 1% by weight or less, the water on the surface of the water absorbent resin can penetrate quickly into the water absorbent resin itself when it penetrates into the water absorbent resin itself, and as a result, the water absorbent resin itself can swell quickly. If the water soluble component exceeds 1% by weight, the water soluble component hinders the water from penetrating into the water absorbent resin, so the swelling is slowed down. That is, since the water-absorbent resin in the gelling material swells more quickly than before, the bag can be opened by being pushed open more quickly, and the aqueous liquid on the outside can be gelled.

[0048] The aqueous liquid to which the gelling material of the present invention is applied may be a water-containing liquid, and is not particularly limited. The proportion of water in the aqueous liquid is not particularly limited, but is preferably 50% by mass or more. Specific examples of the aqueous liquid include general water such as rainwater, tap water, well water, river water, pond / lake water, seawater, and muddy water; sludge-like wastewater and waste liquid generated from mines, civil engineering and construction sites, paper and pulp factories, textile and dyeing factories, machine and metal processing factories, ore refining factories, chemical factories, electrical and electronic factories, medical industry facilities such as hospitals, food processing factories, ceramics, water purification plants, sewage treatment plants, and homes. The liquid may be in a stationary state or in a flowing state.

[0049] The gelling material of the present invention can gel the aqueous liquid in a short time (usually about 1 minute) by adding it to an aqueous liquid and stirring the entire liquid. The ratio of the water absorbent resin in the gelling material to the water in the target aqueous liquid is preferably 1:500 to 1:10 by mass, and particularly preferably 1:400 to 1:50. Stirring is sufficient to lightly mix the entire liquid. A general-purpose stirrer can be used, and there is no particular limitation. If the liquid volume is 5 liters or less, stirring by hand using a spatula is sufficient.

[0050] The present invention is applied to any one of the following applications: water-absorbing bags, water-absorbing sandbags, and sludge volume reduction bags, which are characterized by using the gelling material for aqueous liquids. Water-absorbing bags are used, for example, when a ground becomes soaked after rain, to absorb and remove water, thereby quickly drying the ground. Water-absorbing sandbags are used to hold back water during floods, like sandbags made of sand. Sludge volume reduction bags allow water in sludge to seep into the bag, and absorb the water to reduce the water in the sludge, which results in a reduction in the apparent amount of sludge, thereby reducing the overall volume of sludge. All of these are constructed with the same structure and can be applied to different applications. Below, we will explain water-absorbing sandbags as a representative example.

[0051] The water-absorbent sandbag is formed by sealing the gelling material of the present invention in a water-permeable bag. The material of the water-permeable bag can be the same as that of the sheet water-permeable bag described above. The size of the bag is not particularly limited as long as it can seal the gelling material of the present invention, but is preferably 20 to 50 cm x 50 to 80 cm, more preferably 30 to 45 cm x 50 to 70 cm. The shape of the bag is also not limited, as with the gelling agent. The water-absorbent sandbag seals preferably 1 to 10 pieces of the gelling material of the present invention, more preferably 1 to 6 pieces, and particularly preferably 1 to 4 pieces. If the gelling material is fixed in the water-absorbent sandbag with double-sided tape so that the gelling material is uniformly spaced apart, the gelling material will not move or become biased during transportation, and uniform gelation will occur when used. The width of the gap is preferably 1 to 15 cm, particularly preferably 3 to 10 cm. The ratio of the gelling material of the present invention to the area of ​​the bag constituting the water-absorbent sandbag is preferably 10 to 70%, and particularly preferably 20 to 50%.

[0052] FIG. 1(a) is a perspective view showing the structure of an absorbent sandbag in accordance with the present invention, and FIG. 1(b) is a perspective view showing the absorbent sandbag of FIG. 1(a) in a swollen state after being immersed in water. When the water-absorbing sandbag 1 in Fig. 1(a) is immersed in water, the gelling material 2 collapses and expands the burlap bag 3 that is the packaging. This state is shown in Fig. 1(b) as the swollen water-absorbing sandbag 5. The water-absorbing sandbag of the present invention can be used in the same way as an ordinary sandbag, but can also be suitably used to prevent the intrusion of rainwater to protect embankments, buildings, houses, etc., during floods, heavy rains, etc.

[0053] The present invention will be further described below with reference to examples, but the present invention is not limited thereto. Manufacturing Example 1 76.7g of sodium acrylate, 23g of acrylic acid, 0.3g of N,N'-methylenebisacrylamide and 295g of deionized water were placed in a 1-liter glass reaction vessel, and the temperature of the contents was maintained at 5°C while stirring and mixing. Nitrogen was introduced into the contents to adjust the dissolved oxygen content to approximately 1 ppm, and then 1g of a 1% aqueous solution of hydrogen peroxide, 1.2g of a 0.2% aqueous solution of ascorbic acid and 2.8g of a 2% aqueous solution of 2,2'-azobisamidinopropane dihydrochloride were added and mixed to initiate polymerization (polymerization concentration: 25%). A hydrous gel polymer was obtained by polymerization and aging for approximately 6 hours. This hydrogel polymer was layered to a thickness of 5 cm on a SUS screen with an opening of 850 μm, and a small air permeation dryer (manufactured by Hakko Electric Manufacturing Co., Ltd.) was used to permeate the hydrogel for 30 minutes under conditions of a supply air temperature of 205°C and an air speed of 1.5 m / sec. The hydrogel was then heated and dried to obtain a dried material with a moisture content of about 4%. The dried material obtained was pulverized using a household mixer, and particles with a particle size of 32 to 710 μm (400 mesh to 22 mesh) were collected using a sieve, and the resulting product was treated as a water-absorbent resin (1) (average particle size 420 μm, water absorption ratio 220 times, gel strength 31,000 dynes / cm). 2 The water-soluble component content was 6.5% by weight.

[0054] Manufacturing Example 2 A water absorbent resin (2) (average particle size: 375 μm, water absorption capacity: 205 times, gel strength: 35,000 dyne / cm) was prepared in the same manner as in Production Example 1, except that 285 g of deionized water was used instead of 295 g of deionized water, 3.2 g of a 2% aqueous solution of 2,2'-azobisamidinopropane dihydrochloride was used instead of 2.8 g of the 2% aqueous solution of the same, and polymerization and aging were performed for about 8 hours instead of about 6 hours. 2 The water-soluble component content was 0.9% by weight.

[0055] Production Example 3 100 g of the water absorbent resin (2) was added to 1 g of "Aerosil 200CF" (hydrophilic ultrafine silica particles, average particle diameter of primary particles is about 12 nm, manufactured by Nippon Aerosil Co., Ltd.) in a V-type mixer, and thoroughly stirred to obtain a water absorbent resin A of the present invention in which the surface of the water absorbent resin (2) was coated with ultrafine silica particles.

[0056] Production Example 4 In Production Example 3, 0.5 g of "Aerosil 200CF" and 0.5 g of "Aerosil R972CF" (hydrophobic ultrafine silica, average particle size of primary particles is about 16 nm, manufactured by Nippon Aerosil Co., Ltd.) were used instead of 1 g of "Aerosil 200CF" in the same manner as in Production Example 3, to obtain a water absorbent resin B of the present invention.

[0057] Production Example 5 A comparative water absorbent resin C was obtained in the same manner as in Production Example 3, except that 100 g of the water absorbent resin (1) was used instead of 100 g of the water absorbent resin (2).

[0058] Example 1 A sheet (a) made by laminating a 30 μm thick poval (PVA) film (Kuraray, CP-1220T10, saponification degree 87-89%) on "Havix JS45HD-W" (Havix, dry pulp nonwoven fabric) was cut into a rectangle measuring 10 x 15 cm, and the PVA film side of the sheet was overlapped and the three edges (sides) were heat sealed to produce a bag. 50 g of the above water-absorbent resin A was placed in the bag, and the opening was then heat sealed (sealed) to produce the gelling material (A) of the present invention.

[0059] Example 2, Comparative Examples 1 to 3 Gelling material (B) (Example 2), gelling material (C) (Comparative Example 1), gelling material (D) (Comparative Example 2), and gelling material (E) (Comparative Example 3) were obtained in the same manner as in Example 1, except that the same amounts of water absorbent resin B, water absorbent resin (2), water absorbent resin C, and water absorbent resin (1) were used instead of water absorbent resin A in Example 1. See Table 1 below.

[0060] The above gelling material was used to carry out the following gelling test. (Test Method) 2 L of tap water was placed in a 3 L plastic beaker, the liquid temperature was adjusted to 25°C, the gelling material was added, and the time (seconds) until the entire tap water gelled was measured. The results are shown in Table 1.

[0062] From Table 1, it is seen that the gelling material of the present invention can gel faster than the conventional gelling material (E). [Explanation of symbols]

[0063] 1. Water-absorbing sandbags 2. Gelling material 3. Hemp bag 4. Stitching of water-absorbing sandbags 5. Swollen, water-absorbent sandbags

Claims

1. A gelling material comprising a powdered and / or granular water absorbent resin wrapped and sealed in a sheet, At least a part of the sheet is water permeable, and at least a part of the sealed portion is sealed with a water-soluble polymer having a weight average molecular weight of 1,000 to 1,000,000; The water-absorbent resin has a water absorption capacity of 80 to 1000 times for pure water and a water-soluble component content of 1% by weight or less; A gelling material for aqueous liquids, characterized in that the water-absorbent resin is treated with silica that is a combination of hydrophilic silica and hydrophobic silica.

2. 2. The gelling material for aqueous liquids according to claim 1, wherein the water-soluble polymer is polyvinyl alcohol.

Citation Information

Patent Citations

  • Liquid-absorptive polymer composition and its manufacture

    JP1990227435A

  • Gelling material for aqueous liquid and gelling method

    JP1992239087A

  • Water-absorbing resin and its production

    JP1996188602A

  • Gelling agent for aqueous solution and sand bag substitute used with the gelling agent

    JP2002105921A

  • Method for reducing amount of waste water stored in container, and bag used therefor

    JP2015155079A